Predictors Of Self-Management In The Elderly With Hypertension In Aceh Besar Regency - ibrahim, Ibrahim; Duana, Maiza (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
Hypertension is one of the most common non-communicable diseases worldwide, with its prevalence increasing with age. Data from the World Health Organization (WHO) shows that about 1.13 billion people in the world suffer from hypertension, and this number is expected to increase to 1.5 billion by 2025. Self-management is becoming an important approach in hypertension management, which includes the ability of individuals to manage their own health through blood pressure monitoring, dietary regulation, physical activity, and adherence to medication. This study aims to explore the influence of factors such as knowledge, social support, physical condition, and access to health services on self-management skills in the elderly with hypertension. The method used was a correlational research design with a cross-sectional approach, involving elderly respondents with hypertension in Aceh Besar. The results of the analysis show that housing conditions and family support are the main predictors in self-management, with the highest R-Square value of 0.840. Knowledge also contributed significantly, while the distance of health services showed a smaller influence. In conclusion, to improve self-management in the elderly with hypertension, it is important to apply a holistic approach that considers social, environmental, and health education factors. Integrated interventions can help the elderly manage their condition more effectively, improve their quality of life, and reduce complications related to hypertension.